Peningkatan Proses Bisnis Kegiatan Carry Over pada Politeknik Caltex Riau - Cakra Ramadhana Ramadhana; Suryanto Elly Chandra (Jurnal Komputer Terapan, 2019)
Politeknik Caltex Riau (PCR) is a college in Pekanbaru, Riau. PCR has business processes, one of which is Carry Over (CO) or short semester. Current business process of CO is not completely optimizing Information System of Academic (SIAK), such as scheduling, CO registration for student, and honorarium distribution for lecturer and/or laboratory assistant. It shows that current business process is not efficient yet and could be affecting business process of organization completely. Therefore, current business process of CO needs to be improved. The purpose is to improve the process for the better CO service for students. The method used for the improvement is Business Process Improvement (BPI), by implementing one of its tools called streamlining. The type of streamlining that is applied in the improvement of CO business processes including upgrading, standardization, bureaucracy elimination, and process cycle-time reduction. After the process improvement, there was a more concise CO service process with a total of 17 activities from the previous 19 activities. Improved CO process is also supported by the utilization of PCR Academic Information System.